PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP KEMAMPUAN MENULIS PUISI SISWA SMA - Eni Emelia; Hetilaniar; Juaidah Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the mind mapping learning model on the poetry writing ability of class X students at SMA Negeri 1 Penukal Utara. The background of this study is based on the low ability of students in writing poetry, especially in finding themes and arranging appropriate diction. The study uses a quantitative approach with an experimental design. The research subjects consisted of two classes, namely the experimental class taught using the mind mapping model and the control class with a conventional learning model, each consisting of 30 students. Data collection was carried out through a poetry writing test at the end of the treatment (post-test). The results showed that the average post-test score of the experimental class students was 73.3, while the control class obtained an average of 56. Hypothesis testing using the Independent Sample t-Test showed a significance value of 0.000 <0.05, which means there is a significant influence of the use of mind mapping on students' poetry writing ability. Thus, the mind mapping learning model is proven to be effective in improving poetry writing ability because it helps students develop ideas, structure poetry, and enrich the use of language creatively.